PENERAPAN MODEL PEMBELAJARAN KOPERATIF TIPE STAD BERBANTUAN MEDIA CARD SORT UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KONSEP PESAWAT SEDERHANA - Sari, Meutia (Prosiding Temu Ilmiah Nasional Guru, 2023)
This research is motivated by the lack of maximum ability of students in understanding science subjects, especially in the Physics material for simple aircraft chapters. Based on the results of initial observations on learning and the results of the final test conducted on class VIII students of SMPS Tiara school Bogor, only 66.7% of students mastered the material. The purpose of this study was to describe the procedure for applying Card Sort image media and applying the STAD type learning model to improve students' ability to understand simple machine material and understand its benefits in everyday life. The subjects of this study were 12 grade VIII students of SMPS Tiara School, consisting of 6 female students and 6 male students. The results showed that the final test result of cycle 1 had an average score of 66.7% and increased in the final test of cycle 2, which was 91.3%. This level of achievement is quite high because almost all students score above the KKM, while the KKM applied for science material is 70. The application of the STAD type learning method assisted by card sort media can improve students' understanding of simple airplane material.